A low-cost phenylbenzoimidazole containing electron transport material for efficient green phosphorescent and thermally activated delayed fluorescent OLEDs. Issue 21 (7th June 2015) - Wang, Fangfang; Hu, Jia; Cao, Xudong; Yang, Tao; Tao, Youtian; Mei, Ling; Zhang, Xinwen; Huang, Wei
<x xml:space="preserve">Abstract</x> A new electron-transport iTPBI-CN material synthesized through a simple low-cost reaction exhibited a much higher efficiency than commercial TPBI in green OLEDs.